Pengaruh Return On Assets, Net Profit Margin, , Earning Per Share Dan Return On Equity Terhadap Harga Saham (Studi Pada Perusahaan food and beverages yang Terdaftar di BEI tahun 2012-2015) - Resdiyanto, Jefri; , Sri Murwanti S.E., MM (2016)
This study aims to examine the Return on Assets, Net Profit Margin, erning per share, return on equity on stock price. The research population is food and beverages company listed on the Stock Exchange. The sampling method using purposive sampling with criteria established that annual reports from 2012 to 2015. The number of samples were analyzed using multiple linear regression analysis. Based on test results hepotesis variable Return On Assets (ROA) positive effect on stock price. Variable Net Profit Margin (NPM) no positive effect on stock price. Variable erning per share (EPS) positive effect on stock price. Variable Return On Equity (ROE) no positive effect on stock price. F simultaneously test four variables ROA, NPM, EPS and ROE significantly affect the stock price.